Dinoflagellate cyst distribution during the middle eocene in the drake passage area: paleoceanographic implications - González Estebenet, María Sol (2014)
Fil: González Estebenet, María Sol. Instituto Geológico del Sur. Departamento de Geología. Universidad Nacional del Sur. Bahía Blanca; Argentina